Fluorescence turn-on detection of mercury ions based on the controlled adsorption of a perylene probe onto the gold nanoparticles. Issue 1 (30th November 2015) - Li, Juanmin; Chen, Jian; Chen, Yang; Li, Yongxin; Shahzad, Sohail Anjum; Wang, Yan; Yang, Meiding; Yu, Cong
Abstract : A novel fluorescence turn-on strategy based on Au nanoparticles and a perylene probe for the sensing of Hg 2+ ions has been developed. Abstract : A novel fluorescence turn-on strategy based on Au nanoparticles and a perylene probe for the sensing of Hg 2+ ions has been developed. It was observed that a perylene probe could be adsorbed onto the surface of Au NPs through strong electrostatic and hydrophobic interactions. Its fluorescence was efficiently quenched by the Au nanoparticles. However, in the presence of Hg 2+ and NaBH4, Hg 2+ was reduced and an Au/Hg amalgam was formed on the surface of the Au nanoparticles. The perylene probe could hardly be adsorbed and quenched by the Au/Hg amalgam. A turn on fluorescence signal was therefore detected. The assay is quite sensitive, and 5 nM Hg 2+ could be easily detected. It is also very selective, a number of metal ions were tested and no noticeable interference was observed. The assay was also successfully applied for the determination of Hg 2+ in lake water samples. A simple, fast, inexpensive, highly sensitive and selective Hg 2+ sensing strategy is therefore established.